A REVIEW: LOVASTATIN PRODUCTION AND APPLICATIONS - K V, Radha; D, Lakshmanan (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Cholesterol is an organic compound, which is produced in humans by a complex metabolism. It acts as a precursor for the synthesis of many steroids, vitamin D and also helps in membrane transport. Increase of cholesterol in humans, leads to Cardio Vascular Disorders and finally death. This can be reduced by inhibiting the HMG-CoA reductase, which is an important precursor in formation of mevolanate from Acetyl CoA. Inhibition is done by statin drug, which is produced by many fungi through polyketide pathway. Many fungus produce lovastatin, while other statins like rosuvastatin, simvastatin, pravastatin, fluvastatin are synthesized from lovastatin and mevastatin. Other than reduction of cholesterol, lovastatin is shown to provide various medicinal properties like anti-cancer, bone maturation, multiple sclerosis. In this review, a detailed note on various organisms employed for the production of lovastatin and different fermentation techniques for the same was studied. This review also helps in understating the inhibition of HMG-CoA reducatse and various medicinal properties of lovastatin. Keywords: Lovastatin, Fungus, Submerged fermentation, Solid state fermentation, HMG-CoA reducatse.